The impact of an organized physical activity program on the health indicators of students from differ-ent cultural groups in second chance school setting - Sotirios Vousiopoulos; Olga Kouli; Helen Douda; Vasiliki Derri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The primary objective of this research was to assess the impact of a structured physical activity program on the health indicators of adult students attending a multicultural Second Chance School (SCS). The study encompassed a total of 62 SCS students aged 19 to 57, who were divided into two groups: experimental and control. The intervention program consisted of two sessions per week spanning 20 weeks, with each session lasting 60 minutes. The exercise intensity ranged from 65% to 85% of HRmax and included various activities such as aerobics, weight exercises, dumbbell routines, and hiking. Measurements were taken at both the commencement and conclusion of the organized physical activity program. Specialized equipment, including a wall-mounted stadiometer, precision scales, a unique tape measure, an automated sphygmomanometer, and the DXA machine, was employed for data collection. Data analysis involved ANOVA variance analyses, descriptive statistics, and T-Tests utilizing the SPSS software. The results revealed a statistically significant primary influence attributed to the 'measurement' factor (p<.001) across all health indicators, except for total BMD and total BMC, when comparing the experimental and control groups. In terms of gender disparities, men exhibited higher measurements in body mass, fat-free mass, belly size, and blood pressure, while women displayed greater fat mass and total body fat. To conclude, the intervention program had a positive impact on improving the health indicators of adult SCS students. Future research endeavors should explore the implementation of Physical Activity programs in other SCSs throughout Greece.